Cross-reactive immunity against the SARS-CoV-2 Omicron variant is low in pediatric patients with prior COVID-19 or MIS-C - Juanjie Tang; Tanya Novak; Julian Hecker; Gabrielle Grubbs; Fatema Tuz Zahra; Lorenza Bellusci; Sara Pourhashemi; Janet Chou; Kristin Moffitt; Natasha B. Halasa; Stephanie P. Schwartz; Tracie C. Walker; et al. (Nature Communications, 2022)
The antibody response to the SARS-CoV-2 Omicron variant is not well studied in children. Here, the authors provide an age-stratified analysis of SARS-CoV-2 neutralizing capacity of sera from children with acute or convalescent COVID-19 as well as children with multisystem inflammatory syndrome.